America between the wars, 1919-1941 : a documentary reader - Welky, David (Malden, MA : Wiley-Blackwell, 2012)
'With the Great Depression, the growth of a consumerist mass culture, the reshaping of government under Franklin Roosevelt's New Deal, and intense debates over race and the role of women, the 22 years of peace that spanned America's involvement in two world conflicts was a period of exceptional social, political, economic, and cultural upheaval in the United States. This compact, yet authoritative, collection places over seventy of the most important documents from 1919-1941 in their historical context and offers insights into the American experience during the interwar era and the many developments that were crucial to the creation of present-day United States. Taking in such familiar names as Warren Harding, Charles Lindbergh, and Franklin Roosevelt as well as writings by the ordinary people who had little individual control over the sweeping changes and developments of a tumultuous age, this collection provides coverage of the themes, struggles, and events that characterized the 1920s and 1930s. With photographs and illustrations, end-of-chapter questions, and coverage of topics from new trends in literature to isolationism and the debate over American involvement in World War II, this book invites readers to engage actively in historical interpretation and to gain a thorough understanding of the interplay between social and political forces in the historical developments of the period'--
Includes bibliographical references and index.
Keywords: United States -- History -- 1919-1933 -- Sources; United States -- History -- 1933-1945 -- Sources; United States -- Social conditions -- 1918-1932 -- Sources; United States -- Social conditions -- 1933-1945 -- Sources